Discrere mathematics : with graph theory and combinatorics - Veerarajan, T (Tata McGraw-Hill, 2007)
Discrere mathematics : with graph theory and combinatorics / Veerarajan, T. -- New Delhi: Tata McGraw-Hill, 2007 511.3 V419 No. of Copies : 1